Current status of brucellosis in Latin America - Szyfres, Boris (1958)
The authors have summarized the information available to them regarding the problem of human and animal brucellosis in Latin America. Animal brucellosis in Latin American countries is a widespread infection. In cattle attacked in preference to animal milk which reaches its highest prevalence. The suina and caprine brucellosis is second in magnitude. In beef cattle, the infection is lower than in the previous groups, and in sheep there is a small percentage of reactants significant title, there being no verification based on isolation of the germ. Human brucellosis is closely linked to the exploited animals spice. In regions where goats infection predominates the most important vehicle of human infection is ingestion of milk and dairy products. However, where the predominant bovine brucellosis, contact with animals is the main way of transmission to humans. The importance of contact with animals is demonstrated by serological surveys in occupational groups and the general population groups in several countries.